STUDY CONCERNING ELECTION OF PROCUREMENT METHOD IN PROJECT CONSTRUCTION IN INDONESIA - ISNARNO ISNARNO (Fakultas Teknik Universitas Tunas Pembangunan Surakarta, 2010)
Procurement method is one of the steps or sub-sistems in construction project. There are some procurement methods expanding in Indonesia, for example : Conventional method, Design / Build method, Turnkey method and Management Construction method. Accuracy in choosing procurement method the will have an effect on in execution of construction project: speed of execution, cost, quality, involvement from every party. This research aims to analyse factors influencing election of procurement method in construction project in Indonesia. The gathering data has done by spreading questionnaire to Jakarta, Semarang, Solo, Purwokerto, Yogyakarta and Surabaya. From questionnaires which were returned, 30 questionnaire could be processed. Result of data analysis in this research indicate that factor influencing election of qonventional method are quality level, point of responsibility and certainty. Factor influencing election of Design I Build method are quality level, price competition and complexity. Factor influencing election of Turnkey method are certainty, risk avoidance and flexibility. Factor influencing election of Management Construction method are quality level, price competition and point of responsibility. And factor influencing election of procurement method in general are quality level, certainty and price competition